2020
DOI: 10.1016/j.jdin.2020.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Paraffin-embedded tulle nets as a simple dressing technique for patients with pemphigus

Abstract: Pemphigus, a blistering disease, commonly presents with extensive, superficial, painful, moist, cutaneous erosions requiring appropriate systemic therapy and scrupulous high-quality wound care. Historically, paraffin waxes have been used for the treatment of wounds and burns. Despite the availability of nonadherent dressings, they are often difficult to secure to the wet wound bed. 1,2 SOLUTION We practice a simple dressing method developed by Mohan Gharpuray, FRCP (Maharashtra Medical Foundation, Pune, India)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…One study suggested paraffin‐embedded tulle nets for pemphigus wounds. This modality was considered an easy to apply and remove dressing for PV wounds offering significant improvement in patients' quality of life 10 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One study suggested paraffin‐embedded tulle nets for pemphigus wounds. This modality was considered an easy to apply and remove dressing for PV wounds offering significant improvement in patients' quality of life 10 …”
Section: Resultsmentioning
confidence: 99%
“…It is a safe and easy-to-apply alternative without having any severe adverse effects. 10 Based on our study, there is a sparse number of randomized controlled studies (RCT)s evaluating the efficacy of topical dressings in the management of pemphigus lesions. Due to the few available studies in this field, a definite suggestion cannot be made, which can be considered as the limitation of our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations